2006
DOI: 10.1016/j.dci.2005.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulins of the non-galliform birds: Antibody expression and repertoire in the duck

Abstract: Galliform and non-galliform birds express three immunoglobulin isotypes, IgM, IgA and IgY. Beyond this we should not generalize because differences in gene organization may have functional consequences reflected in the immune response. At present, studies on non-galliform birds are largely restricted to ducks. Ducks express an alternatively spliced form of their IgY heavy chain (upsilon) gene, the IgY(DeltaFc), that lacks the Fc region and Fc-associated secondary effector functions. It is not known how common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(48 citation statements)
references
References 42 publications
0
46
1
1
Order By: Relevance
“…To our knowledge, IgY has previously been described only in birds and amphibians (Warr et al, 1995;Lundgvist et al, 2006), and its discovery in the turtle fills up the gap in the knowledge IgY in vertebrates.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…To our knowledge, IgY has previously been described only in birds and amphibians (Warr et al, 1995;Lundgvist et al, 2006), and its discovery in the turtle fills up the gap in the knowledge IgY in vertebrates.…”
Section: Discussionmentioning
confidence: 97%
“…The basic structure of the Igs is composed of a four-chain unit in which two heavy chains are associated with two light chains, and the constant domains define the isotype of Ig heavy chains (Flajnik, 2002). In mammals, five Ig isotypes, IgM, IgD, IgG, IgA and IgE have been reported, and three isotypes, IgM, IgY and IgA in avians (Lundgvist et al, 2006;Schaerlinger et al, 2008). However in anuran amphibians, five isotypes have so far been reported, namely, IgM, IgY, IgX, IgD and IgF, and studies on amphibian Igs have mostly resulted from the model animal Xenopus.…”
Section: Introductionmentioning
confidence: 99%
“…It was consistent with previous studies reporting that ducks typically generated poor antibody responses to influenza compared with mammals or even chickens, and further studies showed immunoglobulin genetics contributed to poor antibody responses to influenza infection or vaccination. Evidence also suggested that lack of secondary immune responses appeared to be a general feature of duck antibody responses (Kida et al, 1980;Lundqvist et al, 2006). Several inactivated influenza vaccines are currently used for controlling avian influenza in the laboratory and field studies (Tian et al, 2005;Nomura et al, 2012;).…”
Section: Discussionmentioning
confidence: 99%
“…In duck billed platypus (Ornithorhynchus anatinus), a much more complicated IgH locus has recently been revealed [3,4], with the finding of two IgA isotypes [5] and a new Ig isotype, IgO [4], which is considered to be a remaining copy of IgY in monotremes [5]. Avian species are reported to have IgM and IgA, and also IgY in duck [6,7], but as IgG in chicken which, from a phylogenetic perspective, is equidistant from mammalian IgG and IgE and which in birds has sometimes been referred to as IgY [8]. Recently, IgM, IgD and IgY genes have been identified in reptile, the green anole lizard (Anolis carolinensis) with available genome data [9], and also in an economically important species [10].…”
Section: Introductionmentioning
confidence: 99%